Case Report: Multiple electrolyte disturbance with severe neurological manifestations induced by chronic use of PPIs - Bertuccioli, Alexander; Cardinali, Marco; Di Pierro, Francesco; Zonzini, Giordano Bruno; Zerbinati, Nicola; Tanda, Maria Laura; Belli, Annalisa; Palazzi, Chiara Maria (Frontiers in Medicine, 2025)
BackgroundProton pump inhibitors (PPIs) are widely prescribed, especially in older adults with multiple comorbidities. However, their long-term use may lead to under-recognized adverse effects, including hypomagnesemia and related electrolyte disturbances, with potential neuromuscular and cognitive consequences.Case presentationAn 84-year-old man with several chronic conditions and prolonged PPI therapy presented with recurrent dysphagia, neuromuscular symptoms, and seizure-like episodes. Laboratory tests consistently showed hypokalemia and hypocalcemia, with intermittent hypomagnesemia, despite ongoing supplementation.InterventionA comprehensive medication review led to the discontinuation of both pantoprazole and Levetiracetam. The Naranjo algorithm was used to assess causality, indicating a probable adverse drug reaction.OutcomeFollowing drug withdrawal, the patient experienced marked clinical improvement, with normalization of electrolyte levels. He no longer required supplementation and maintained stability through dietary management and adjustment of his antihypertensive therapy.ConclusionThis case highlights the dual iatrogenic role of PPIs and antiepileptics in causing persistent electrolyte imbalances. It emphasizes the need for regular medication reviews in elderly, polymedicated patients to prevent functional decline and promote recovery.